Contribution of Compassion International to the Livelihood of Smallholder Farmers in Bushenyi District - Muhumuza, Aryamanya Wycliffe; Ssemakula, Edward; Osiru, David (East African Nature and Science Organization, 2022)
The study was to assess the contributions of Compassion International to the livelihood of smallholder farmers in the Bushenyi district of western Uganda. The specific objectives were to; (i) assess the household livelihood changes resulting from smallholder participation in Compassion International programs; (ii) assess the level of beneficiary participation in Compassion programs, (iii) analyse the contribution of Compassion International to food production and security, and (iv) examine the challenges being faced by Compassion International that hinder their operations in rural settings of Uganda. The study adopted a descriptive survey design that applied both quantitative and qualitative approaches for data collection. Data was captured from 206 respondents using both a questionnaire and an interview schedule. Data was analysed using SPSS version 16 to generate both descriptive and inferential statistics. The study found that smallholder participation in Compassion International programs has resulted in livelihood changes such as; enhanced child education, household economic and spiritual empowerment, increased access to agricultural inputs, income-generating projects, and enhanced household capacities. The study also found that beneficiaries participated in compassion programs by attending organisation outreaches, seminars, and annual meetings, mobilising local resources towards the cause, participating in project activities, paying annual membership fees, and giving feedback on project activities and operations. Compassion International has contributed towards household food production and security of the household across the district by setting up agricultural support projects, mobilising farmers, providing agro-inputs, and facilitating extension service delivery. The study further established that; poor funding, corruption and misuse of funds, competition and poor power relations with the local government are the key challenges hindering Compassion International’s operations in the Bushenyi district. The study concluded that though smallholder farmer participation in compassion programs has resulted in improved livelihood changes for member households, there remains a huge socio-economic gap in the Bushenyi district. The organisations’ operations are still hampered by a number of challenges. The NGO needs to tackle poverty reduction dynamically, strategically, and comprehensively. This is because poverty is a multidimensional phenomenon that needs a multidimensional approach. There is a need to look at other categories of needy people in society such as the elderly, widows, and disabled persons, rather than placing emphasis on a category.